STUDENT AND HISTORY - Andrey L. Andreev (Высшее образование в России, 2016)
The article focuses on the key issues of studying and teaching history in the system of higher education of the Russian Federation, which are considered on the basis of the data of sociological surveys. The author gives a characteristic of the level of students' historical knowledge and their relationship to the academic subject «history». The analysis is differentiated by the integrated groups of specialties (humanities and engineering).